2019
DOI: 10.1093/cid/ciz033
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Infant Colonization by Hypervirulent CC17 Group B Streptococcus: Toward the Understanding of Late-onset Disease

Abstract: The hypervirulent group B Streptococcus clone CC17 accounts for the majority of infant late-onset disease (LOD). We provide evidence that the high incidence of CC17 in LOD is likely due to an enhanced post-delivery mother-to-infant transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 21 publications
2
58
0
Order By: Relevance
“…Besides, HvgA confers gut colonization capacities in murine models and it was presumed that CC17 GBS association with LOD was related to an increased ability of CC17 GBS to colonize neonates compared to other GBS clones (Tazi et al, 2010). However, a recent large prospective cohort study of infant colonization by GBS showed that instead of colonizing neonates more efficiently than other GBS clones, CC17 GBS was associated with a higher risk of delayed post-delivery colonization (Tazi et al, 2019). Together with our findings, these results suggest that the important responsibility of CC17 GBS in LOD relies i) on its improved capacity to establish in the infant developing and versatile microbiota, advantage which is likely conferred by HvgA, and ii) on Srr2-mediated ability to use M cells to cross the intestinal barrier and eventually to disseminate.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, HvgA confers gut colonization capacities in murine models and it was presumed that CC17 GBS association with LOD was related to an increased ability of CC17 GBS to colonize neonates compared to other GBS clones (Tazi et al, 2010). However, a recent large prospective cohort study of infant colonization by GBS showed that instead of colonizing neonates more efficiently than other GBS clones, CC17 GBS was associated with a higher risk of delayed post-delivery colonization (Tazi et al, 2019). Together with our findings, these results suggest that the important responsibility of CC17 GBS in LOD relies i) on its improved capacity to establish in the infant developing and versatile microbiota, advantage which is likely conferred by HvgA, and ii) on Srr2-mediated ability to use M cells to cross the intestinal barrier and eventually to disseminate.…”
Section: Discussionmentioning
confidence: 99%
“…3e5 Vaginal colonization with GBS occurs in approximately 18% of pregnant women worldwide 6 and has been linked with preterm birth (PTB), 2,7e9 preterm premature rupture of membranes (PROM), 10 and neonatal intensive care unit (NICU) admission. 11 GBS vaginal colonization is a risk factor for neonatal transmission during delivery 12,13 and to infants during the postnatal period 14 and is associated with a 3-fold increased rate of NICU admission. 11 GBS in the vagina during pregnancy can also invade through the cervix to cause uteroplacental and fetal infections.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that srr2 transcription requires an activator such as the Rga-associated regulator present in the distantly related srr1 operon of non-CC17 strains (8, 48), which might be necessary to outcompete the binding of the non-phosphorylated CovR form on the promoter. The integration of multiple regulatory proteins might be necessary to express Srr2 preferentially in the neonatal gut rather than during the invasive phase (7, 49), in contrast to HvgA which has a major role at the onset of meningitis (6).…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with the lower haemolytic activity and the higher level of CovR phosphorylation in BM110 compared to NEM316. The paradox of a more efficient repression of virulence genes in the hypervirulent clone might in fact reflect the clinical characteristic of CC-17 strains which are associated with a delayed colonization of the neonatal gut rather than an increase pathogenicity caused by toxin expression (7, 49, 66).…”
Section: Discussionmentioning
confidence: 99%